ANALISA KERUSAKAN PERMUKAAAN JALAN PADA PERKERASAN LENTUR MENGGUNAKAN METODE PAVEMENT CONDITION INDEX (PCI) DAN BINA MARGA 1990 (Studi Kasus : Ruas Jalan Teluk Mesjid – Simpang Pusako) - Lizar Lizar; Mutasawiah Mutasawiah (Racic : Rab Construction Research, 2024)
The teluk mesjid - simpang pusako road section is a cross-province road which is the closest access to the city of Pekanbaru or the Buton crossing port for the Siak and surrounding communities so it is important to maintain road quality performance to stay in good condition. This study aims to determine the condition value on the teluk mesjid - simpang pusako road section so that it can determine the type of road maintenance program. The method used is the Pavement Condition Index (PCI) method and Bina Marga 1990. The average road condition value on the Teluk Mesjid - Simpang Pusako STA (00+000 - 09+400) road section is 83.78. Based on the PCI method, the rating scale from 71 to 85 is included in the Satisfactory rating. The Priority Order Value on the Teluk Mesjid Road Section - Simpang Pusako STA (00+000 - 09+400) is 12.34. Based on Bina Marga 1990 for priority order values > 7 including the category of Routine Maintenance programs. The results of research conducted on the Teluk Mesjid - Simpang Pusako road section are included in the routine maintenance program, the type of handling of damage that occurs is by patching using Cold Mix.